2021
DOI: 10.1002/ecs2.3381
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the survival of unobservable life stages for a declining frog with a complex life history

Abstract: Demographic models enhance understanding of drivers of population growth and inform conservation efforts to prevent population declines and extinction. For species with complex life histories, however, parameterizing demographic models is challenging because some life stages can be difficult to study directly. Integrated population models (IPMs) empower researchers to estimate vital rates for organisms that have cryptic or widely dispersing early life stages by integrating multiple demographic data sources. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 62 publications
(89 reference statements)
2
17
0
Order By: Relevance
“…Our estimate of annual survival indicates that about half of adult spadefoots breeding in 1 year would be expected to survive until the next breeding season, at least under similar conditions to those at our study sites in a relatively wet year. The relative importance of adult survival to western spadefoot population growth could be further elucidated using population models as done for many other amphibians (Caswell 2001, Trenham and Shaffer 2005, Canessa et al 2014, Earl 2019, Rose et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our estimate of annual survival indicates that about half of adult spadefoots breeding in 1 year would be expected to survive until the next breeding season, at least under similar conditions to those at our study sites in a relatively wet year. The relative importance of adult survival to western spadefoot population growth could be further elucidated using population models as done for many other amphibians (Caswell 2001, Trenham and Shaffer 2005, Canessa et al 2014, Earl 2019, Rose et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A positive effect of mortality preceding density dependence seems quite common in structured populations (Abrams 2009;Pardini et al 2009;Loppnow and Venturelli 2014;Schröder et al 2014;McIntire and Juliano 2018) and should be routinely considered in management planning (Zipkin et al 2009;Turner et al 2016), for instance, implementing removal only after density-dependent phenomena (but see Hilker and Liz 2013). The existence of overcompensatory density dependence might also explain why, in native amphibians, low or variable survival rates at early life stages (eggs and tadpoles) have only a minor effect on population growth or decline, in comparison with low post-metamorphic survival rates (Vonesh and De la Cruz 2002;Petrovan and Schmidt 2019;Rose et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies on amphibians have shown that variations in the survival rate of juveniles and sub-adults may have severe population-level effects (Vonesh and de la Cruz 2002;Beaty and Salice 2013;Petrovan and Schmidt 2019;Rose et al 2021). Therefore, it has been recently suggested that both adults and juveniles of guttural toads should be simultaneously removed (Davies et al 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Following the protocol detailed in Kupferberg et al (2012), We used autoregressive time series models to evaluate temporal trends in clutches detected at Alameda Creek. We included mean annual discharge 2 years prior as a predictor variable because population fluctuations of foothill yellow-legged frogs are often driven by the hydrologic conditions affecting recruitment (Rose et al, 2021); the cohort of females that would be breeding for the first time is age 2 in our focal populations (Gonsolin, 2010). We tested for serial autocorrelation in the number of clutches observed because the number of females breeding in a given year is often significantly correlated with the number that laid eggs the previous year (Kupferberg et al, 2012;Rose et al, 2021).…”
Section: Frog Population and Chytrid Disease Monitoringmentioning
confidence: 99%